Pengaruh Perceived Ease Of Use dan Perceived Usefulness Terhadap Niat Menggunakan Uang Elektronik (Studi Kasus Pada Mahasiswa FIA UNKRIS Jakarta) - Syifa, Ghea Ananda; Santoso, Sugeng (PANDITA: Interdisciplinary Journal of Public Affairs, 2024)
The Effect of Perceived Ease of Use and Perceived Usefulness on Intention to Use Electronic Money (Case Study on FIA UNKRIS Students). The purpose of this study was to determine the effect of Perceived Ease of Use and Perceived Usefulness on Intention to Use Electronic Money. This study uses quantitative methods using descriptive analysis and causal associative with survey methods. The population in this study were 396 students consisting of students in semester 3 and above. The sample drawn was 30 respondents based on the descriptive-correlational method using guidelines from the opinion of Husein Umar (2005: 108). The results of this study indicate that there is a significant positive effect of Perceived Ease of Use and Perceived Usefulness on Intention to Use Electronic Money. The magnitude of the influence of Perceived Ease of Use and Perceived Usefulness on Intention to Use Electronic Money is 62.9%.